2016
DOI: 10.1016/j.jacep.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

A High Baseline Electrographic Organization Level Is Predictive of Successful Termination of Persistent Atrial Fibrillation by Catheter Ablation

Abstract: Patients in whom pAF terminated within the LA exhibited a higher level of atrial ECG organization, which was suggestive of a limited number of LA drivers than that of patients in whom the pAF could not be terminated by CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…We show first the application of this algorithm for single-lead ECG signals, and then demonstrate the advantage of using the multi-lead algorithm. We have shown that adaptive, time-variant algorithms outperform methods based on time-invariant band-pass filters (BPF), which could be less accurate for extracting the signal frequency components relevant to AF (Buttu et al, 2016). Here, we used an adaptive frequency tracking scheme to extract: (i) the common oscillatory component present in multi-lead ECG signals, and (ii) the oscillations of the fundamental frequency and its first harmonic from single-lead ECG signals.…”
Section: Calculation Of Ecg Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…We show first the application of this algorithm for single-lead ECG signals, and then demonstrate the advantage of using the multi-lead algorithm. We have shown that adaptive, time-variant algorithms outperform methods based on time-invariant band-pass filters (BPF), which could be less accurate for extracting the signal frequency components relevant to AF (Buttu et al, 2016). Here, we used an adaptive frequency tracking scheme to extract: (i) the common oscillatory component present in multi-lead ECG signals, and (ii) the oscillations of the fundamental frequency and its first harmonic from single-lead ECG signals.…”
Section: Calculation Of Ecg Parametersmentioning
confidence: 99%
“…High DF and low OI values, as measured from the surface ECG, have been shown to predict likelihood of arrhythmia recurrence following CA (Szilágyi et al, 2018), and predictive performance has been shown to increase via the inclusion of adaptive frequency tracking organization parameters (Buttu et al, 2016). Based on these studies, here we compared the values of the IF, AOI, SampEn, and FWA at the three procedure steps outlined in section 2.3, for the three patient groups outlined in section 2.1.…”
Section: Patient Group Comparison At Each Ablation Stepmentioning
confidence: 99%
“…All patients underwent a step-CA procedure consisting of pulmonary vein isolation (PVI), followed by left atrial (LA) CFAEs ablation and linear ablation (roof and mitral isthmus). The stepwise ablation protocol has been described previously (Buttu et al, 2016;Luca et al, 2020). The details of the ablation procedure are also provided in the Supplementary Material.…”
Section: Patient Population and Ablation Proceduresmentioning
confidence: 99%
“…We recently showed that patients with peAF that are unresponsive to step-CA displayed higher AF complexity at baseline as indicated by higher DF values (Luca et al, 2020) and lower ECG-based organization indices (Buttu et al, 2016;McCann et al, 2021) than patients with successful ablation. Furthermore, we found that a step-CA led to increases in surface ECG AF organization in most patients (McCann et al, 2021), without significant differences between patients who remained in sinus rhythm (SR) in the long term and those who did not.…”
Section: Introductionmentioning
confidence: 99%
“…AF termination during stepwise ablation of persistent AF has been reported to predict AF recurrence in several studies. [6,21,8789] The mode of AF termination (directly to sinus rhythm versus via transformation into atrial tachycardia [AT]) was not predictive of recurrence in the majority of studies,but AF termination at index ablation seems associated with a greater proportion of recurrences in the form of AT relative to AF (with a lower total number of arrhythmia recurrences compared to patients without termination). [65,87] This could be explained by differences in the lesion set between patients with termination and without termination, since studies investigating termination used stepwise ablation aimed at AF termination.…”
Section: Functional Endpoints For Af Ablationmentioning
confidence: 99%